DNA Intercalators for Detection of DNA Hybridisation: SCS(MI)–MP2 Calculations and Electrochemical Impedance Spectroscopy. Issue 7 (6th June 2016) - Jambrec, Daliborka; Haddad, Raoudha; Lauks, Anna; Gebala, Magdalena; Schuhmann, Wolfgang; Kokoschka, Malte
Abstract: Quantum mechanical SCS(MI)–MP2/cc‐pVTZ calculations predict the strength of proflavine, ellipticine and 1‐pyrenemethylamine intercalation into single‐stranded (ss) and double‐stranded (ds) DNA. The results were compared with experimental results obtained from electrochemical impedance spectroscopy (EIS). Similar interaction energies of ellipticine with the guanine–cytosine base pair compared to the individual nucleobases guanine and cytosine suggested non‐specific binding also to ssDNA. Accordingly, EIS identified ellipticine as being non‐selective and therefore unsuitable for the detection of DNA hybridisation. The interaction energy of proflavine is significantly higher than the minimum required energy for a single intercalation site, and substantially lower with respect to the minimum energy needed for binding with ssDNA. In EIS studies, proflavine did not show any change in the charge‐transfer resistance with respect to ssDNA and a decrease with respect to dsDNA. Calculations showed that 1‐pyrenemethylamine has sufficiently high interaction energy to intercalate into dsDNA, however, the interaction energy towards ssDNA is close to the minimum required value, suggesting a weak interaction with ssDNA. EIS measurements support the calculations. A method for the calculation of interaction energies is provided, which can be used to characterise the interaction strength between new intercalators and DNA before being synthesised. Abstract : A model sandwich : The prediction of interaction energies using quantum mechanical SCS(MI)–MP2/cc‐pVTZ calculations is presented. These calculations can be used to predict the strength of interactions between intercalators and DNA, allowing the evaluation of the probability of intercalation and the selectivity for dsDNA. Electrochemical impedance spectroscopy was used for comparison and the experimental results are in good agreement with the calculated predictions.